Students' Personal and Academic Attributions of University Withdrawal - Johnson, Genevieve M.; Buck, George H. (Canadian Journal of Higher Education, 1995)
A Commission of Inquiry on Canadian University Education recently reported that approximately 42% of full-time undergraduate students who entered Canadian universities in 1985 failed to obtain a degree within five years. While this statistic is startling, perhaps, of greater concern is the apparent lack of interest shown by most Canadian universities in the subject of undergraduate student attrition. As an initial step toward addressing the issue of Canadian university attrition, a conceptual model of undergraduate student withdrawal is proposed. The model is based on the assumption that students are characterized by a wide range of personal and academic variables. Such characteristics interact or co-exist with institutional variables such as campus integration. This interaction results in the quality of student academic performance and the nature of student psychological condition. Poor quality of student academic performance results in institution-initiated undergraduate withdrawal; a variety of psychological variables (e.g., satisfaction, stress) result in student-initiated undergraduate withdrawal. The bases of this model were findings obtained from questioning 498 undergraduate students who had withdrawn from a large Western Canadian university. Personal student characteristics, institutional factors and societal variables frequently emerged as students' attributions of university withdrawal. Student academic performance was validated as the causal factor for institutional-based undergraduate withdrawal and student psychological state appeared critically related to student-based undergraduate withdrawal. From these findings, preadmission counseling, academic and personal student support and an increased commitment to accommodating students are recommended.